The interests of the United States and China in allying respectively with India and Pakistan since 2000. - Mehrotra, Ankur (2015)
This thesis analyzes the interests of the United States and China in allying respectively with India and Pakistan since 2000. It does so from a realist perspective and uses a qualitative methodology, including the collection and analysis of data from official sources, such as academic articles, magazines, newspapers, think tanks and books. The turn of the century brought structural changes in the global scenario. The United States pivoted to Asia and forged a new alliance with India in order to maintain its global power and hegemony creating a new alliance with India. In particular, China’s mammoth rise became a cause of concern for the United States. I argue that the United States has had three main interests for forging an alliance with India: to maintain its economic power, to contain China and to combat terrorism. Importantly, the two first interests can be understood from a balance-of-power perspective. Meanwhile, China has maintained a strong alliance with Pakistan in order to repeal the United States attempt to encircle it, and to gain regional as well as global leadership. From a balance- of-power perspective China’s main interests in allying with Pakistan are thus the containment of India as an emerging regional power and the maintenance of its regional leadership.